1997
DOI: 10.1002/(sici)1097-0231(19971030)11:16<1794::aid-rcm79>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Time-of-flight-secondary ion mass spectrometry of NaBF4: a comparison of atomic and polyatomic primary ions at constant impact energy

Abstract: (CsI) n Cs + projectiles, n = 0-3, were used to bombard a NaBF 4 (sodium tetrafluoroborate) target at the limit of single ion impacts. The relative yields of ions sputtered from the target were measured and are compared as a function of the number of atoms in the primary ion. When normalized to the mass of the primary ion, sputtered ions that do not resemble the original sample composition, (NaF) n F -, increase in yield as the primary ion complexity increases. The yields of atomic species and polyatomic ions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
3
16
0
Order By: Relevance
“…The preferred loss of BF 3 units, in the case of NaBF 4 , is consistent with the disproportionation of NaBF 4 into NaF and BF 3 , which has been observed most dramatically during studies of secondary ion emission from solid NaBF 4 stimulated by the impact of energetic ions 28–32. For example, the positive secondary ion mass spectra generated by MeV energy ion impacts (fission fragments from 252 Cf) on solid targets composed of NaBF 4 were dominated by a series of cluster ions following the trend (NaF) n Na + , including enhanced intensities at several ‘magic number’ values of n such as 4 and 7 31.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The preferred loss of BF 3 units, in the case of NaBF 4 , is consistent with the disproportionation of NaBF 4 into NaF and BF 3 , which has been observed most dramatically during studies of secondary ion emission from solid NaBF 4 stimulated by the impact of energetic ions 28–32. For example, the positive secondary ion mass spectra generated by MeV energy ion impacts (fission fragments from 252 Cf) on solid targets composed of NaBF 4 were dominated by a series of cluster ions following the trend (NaF) n Na + , including enhanced intensities at several ‘magic number’ values of n such as 4 and 7 31.…”
Section: Resultssupporting
confidence: 69%
“…Because of the potentially labile nature of this Lewis acid/base complex, one might expect the use of relatively high energy desorption and/or ionization methods (such as keV or MeV ion impacts and laser radiation) to hinder, to some degree, the generation of intact, gas‐phase oligomers of NaBF 4 or KBF 4 . For example, in previous experiments involving the sputtering of NaBF 4 by keV and MeV energy ions, such as in secondary ion and plasma desorption MS, the negative ion mass spectra have been shown to contain (in proportions that depend on the projectile complexity, mass and energy) F − , the intact BF 4 − anion and a larger cluster ion such as (MBF 4 )BF 4 − , where M denotes the metal cation 28–30. In all cases thus far, however, the positive ion mass spectrum is dominated by a cluster series following the trend (MF) n M + , including intensity maxima at certain ‘magic number’ ions that adopt stable, cuboid‐like structures 28,.…”
mentioning
confidence: 96%
“…This appears to be particularly prominent in the case of negatively charged ions; noteworthy is the very abundant formation of anionic fluoride molecules from many samples. Although several studies have examined such fluoride anions in the past [9][10][11][12][13][14][15], their possible formation and ionization processes and relative abundances are still not known in detail. (A comprehensive review on molecular anions can be found in [16]).…”
Section: Introductionmentioning
confidence: 99%
“…Polyatomic primary ions proved to be more efficient for producing both high and low mass secondary ions. 8 Interestingly, the relative yield enhancement of ions BF 4 À and NaBF 4 Á BF 4 À reached a plateau value at high primary ion mass, whereas that of (NaF) n Á F À continued to increase. This trend pointed to overlapping collision cascades.…”
Section: 9mentioning
confidence: 99%